2020
DOI: 10.1186/s40035-019-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the micro-environment on α-synuclein conversion and implication in seeded conversion assays

Abstract: Background: α-Synuclein is a small soluble protein, whose physiological function in the healthy brain is poorly understood. Intracellular inclusions of α-synuclein, referred to as Lewy bodies (LBs), are pathological hallmarks of αsynucleinopathies, such as Parkinson's disease (PD) or dementia with Lewy bodies (DLB). Main body: Understanding of the molecular basis as well as the factors or conditions promoting α-synuclein misfolding and aggregation is an important step towards the comprehension of pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 130 publications
(150 reference statements)
1
49
0
Order By: Relevance
“…The use of recombinant aSyn monomers purified from E. coli (Huang et al, 2005) enables studying and inducing aSyn fibril formation in a very controlled and clean environment. For this, different protocols can be applied, however, many involve constant agitation (120-1,000 rpm) for different timeframes in different buffer systems (Narkiewicz et al, 2014;Candelise et al, 2020). It was also described, that the addition of a single glass or PTFE (poly tera-flour-ethylene) bead enhances the formation of aSyn fibrils (Buell et al, 2014;Narkiewicz et al, 2014).…”
Section: Structural Aspects Of Asyn Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of recombinant aSyn monomers purified from E. coli (Huang et al, 2005) enables studying and inducing aSyn fibril formation in a very controlled and clean environment. For this, different protocols can be applied, however, many involve constant agitation (120-1,000 rpm) for different timeframes in different buffer systems (Narkiewicz et al, 2014;Candelise et al, 2020). It was also described, that the addition of a single glass or PTFE (poly tera-flour-ethylene) bead enhances the formation of aSyn fibrils (Buell et al, 2014;Narkiewicz et al, 2014).…”
Section: Structural Aspects Of Asyn Pathologymentioning
confidence: 99%
“…Interestingly, a different fibrillary architecture was found for MSA patients, where the cellular source of aggregated aSyn is not neuronal, but stems from oligodendrocytes ( Shahnawaz et al, 2020 ). Hence, the cellular environment seems to influence the aggregation pattern and fibrillary structure of aSyn significantly ( Candelise et al, 2020 ). Thus, high-resolution structural comparison of GIT- and CNS-derived aSyn conformers could help to better understand the role of the gut-brain axis in PD.…”
Section: Structural Aspects Of Asyn Pathologymentioning
confidence: 99%
“…In particular, MSA and PD strains seem to have different structural and seed properties that may be used as differential diagnostic criteria and that could explain the more aggressive and rapid progression of MSA compared to other synucleinopathies (Peng et al, 2018b ; Candelise et al, 2019 ; Yamasaki et al, 2019 ; Schweighauser et al, 2020 ; Shahnawaz et al, 2020 ; Van Der Perren et al, 2020 ). It is not yet clear how the different α-syn strains are generated, but the cellular micro-environment may play an important role (Candelise et al, 2020 ). Thus, a recent publication by the group of Virginia Lee showed that the α-syn extracted from GCIs presents a different proteolytic profile and more potent biological activity than the α-syn from LBs and that the specific cellular milieu of oligodendrocytes is responsible for the transformation of misfolded α-syn into the MSA strain (Peng et al, 2018a ).…”
Section: Aggregation and Spreading Of α-Synmentioning
confidence: 99%
“…However, very few studies have focused on the effects of intracellular alpha-synuclein (and its pathologic forms) on immune cells. Several observations suggest that such effects may take place and be relevant for disease: (i) some studies have shown that the local environment may be at least partly responsible for alpha-synuclein pathology, which can therefore take place also in immune cells ( Candelise et al, 2020 ) (ii) genetic aberrations such as point mutations, duplications, and triplications are systemic and found also in immune cells ( Gardai et al, 2013 ; Haenseler et al, 2017 ) (iii) alpha-synuclein is capable of escaping into the intracellular space after uptake by cells ( Freeman et al, 2013 ; Flavin et al, 2017 ). The detailed study of the effects of intracellular alpha-synuclein on immune cells bears potential in two main aspects: It may reveal so-far-overseen mechanisms of neuroinflammation, and can hold diagnostic value, as peripheral immune cells are easily accessible.…”
Section: Introductionmentioning
confidence: 99%